2011
DOI: 10.4061/2011/130970
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Lbx1 Expression in Mouse Embryonic Stem Cell-Derived Phenotypes

Abstract: Transcription factor Lbx1 is known to play a role in the migration of muscle progenitor cells in limb buds and also in neuronal determination processes. In addition, involvement of Lbx1 in cardiac neural crest-related cardiogenesis was postulated. Here, we used mouse embryonic stem (ES) cells which have the capacity to develop into cells of all three primary germ layers. During in vitro differentiation, ES cells recapitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…The ladybird protein is a member of the homeobox transcription factor family with an engrailed repressor domain [ 22 ]. In vertebrates, Lbx genes are expressed in the dorsal spinal cord and hindbrain [ 23 ], a subpopulation of cardiac neural crest cells [ 24 ], muscle precursor cells, and satellite cells of regenerating adult skeletal muscle [ 25 , 26 ]. Ectopic expression of LBX1 in chicken somites and limbs activates myogenic markers such as myogenin and myod , owing to the expansion of the myoblastic cell population [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ladybird protein is a member of the homeobox transcription factor family with an engrailed repressor domain [ 22 ]. In vertebrates, Lbx genes are expressed in the dorsal spinal cord and hindbrain [ 23 ], a subpopulation of cardiac neural crest cells [ 24 ], muscle precursor cells, and satellite cells of regenerating adult skeletal muscle [ 25 , 26 ]. Ectopic expression of LBX1 in chicken somites and limbs activates myogenic markers such as myogenin and myod , owing to the expansion of the myoblastic cell population [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LBX1 gene plays an essential role in regulating muscle precursor cell migration and maintaining its migratory potential ( Figure 1 ) (Brohmann et al, 2000 ). Previous transcript analyses and immunofluorescence staining confirmed the upregulation and location of LBX1 in muscle precursor cells (Schmitteckert et al, 2011 ). Migratory muscle precursor cells could remain undifferentiated during migration, and LBX1+ cells commence differentiation into skeletal muscle cells after arrival in the limb (Tani-Matsuhana et al, 2018 ).…”
Section: The Function Of the Lbx1 Gene In Muscle Developmentmentioning
confidence: 71%
“…Muscle hypertrophy depended on the increasing of myofibrils and of the nucleus which relayed on fusion of satellite cells (Campion et al, 1981). Functionally, Lbx1 could induce myogenesis through guiding muscle precursor migration to the proper regions (Schafer and Braun 1999;Schmitteckert et al, 2011) and controlling myoblasts proliferation (Mennerich and Braun, 2001;Martin and Harland, 2006). Furthermore, Lbx1 played important roles in satellite cells differentiation and self-renew (Watanabe et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…During myogenesis in mammals and amphibians, Lbx1 was necessary for the the migration of muscle precursor cells (Jagla et al, 1997;Schafer and Braun, 1999;Gross, et al, 2002;Schafer et al, 2003;Cheng et al, 2005;Martin and Harland, 2006;Wotton et al, 2008;Schmitteckert et al, 2011;). Previous studies have demonstrated that Lbx1 and Pax3 were co-expressed in all migration hypaxial muscle precursors (Gross, et al, 2000).…”
Section: Introductionmentioning
confidence: 97%